2010
DOI: 10.1182/blood-2009-08-238972
|View full text |Cite
|
Sign up to set email alerts
|

PfPI3K, a phosphatidylinositol-3 kinase from Plasmodium falciparum, is exported to the host erythrocyte and is involved in hemoglobin trafficking

Abstract: Polyphosphorylated phosphoinositides (PIPs) are potent second messengers, which trigger a wide variety of signaling and trafficking events in most eukaryotic cells. However, the role and metabolism of PIPs in malaria parasite Plasmodium have remained largely unexplored. Our present studies suggest that PfPI3K, a novel phosphatidylinositol-3-kinase (PI3K) in Plasmodium falciparum, is exported to the host erythrocyte by the parasite in an active form. PfPI3K is a versatile enzyme as it can generate various 3-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
144
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(155 citation statements)
references
References 36 publications
7
144
1
2
Order By: Relevance
“…These lipids are generally not found in unicellular organisms, where only class III PI3-kinases are present. A recent publication reports that P. falciparum PfPI3-kinase immunoprecipitated from infected red blood cell extracts was capable of phosphorylating PI, PI4P, and PI(4,5)P 2 in vitro (54) and could explain the presence of PI(3,4)P 2 and PI(3,4,5)P 3 that we observed in P. falciparum-infected erythrocytes. Our results clearly showed that in intact P. falciparum-infected erythrocytes, PI3P is by far the most abundant phosphoinositide phosphorylated at position 3 (87.5% Ϯ 6.1% [mean Ϯ SEM; n ϭ 8]).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…These lipids are generally not found in unicellular organisms, where only class III PI3-kinases are present. A recent publication reports that P. falciparum PfPI3-kinase immunoprecipitated from infected red blood cell extracts was capable of phosphorylating PI, PI4P, and PI(4,5)P 2 in vitro (54) and could explain the presence of PI(3,4)P 2 and PI(3,4,5)P 3 that we observed in P. falciparum-infected erythrocytes. Our results clearly showed that in intact P. falciparum-infected erythrocytes, PI3P is by far the most abundant phosphoinositide phosphorylated at position 3 (87.5% Ϯ 6.1% [mean Ϯ SEM; n ϭ 8]).…”
Section: Discussionsupporting
confidence: 61%
“…The food vacuole is a compartment with "lysosome-like" functions in Plasmodium, and association of PI3P with its membrane is in accordance with the PI3P-mediated function in transport to- ward the lysosome in other organisms. Indeed, it has very recently been shown that treatment of parasite cultures with the PI3-kinase inhibitors wortmannin and LY294002 inhibited endocytosis within the parasite, resulted in entrapment of hemoglobin vesicles in the parasite cytoplasm, and prevented their fusion with the food vacuole, suggesting that PI3-kinase is involved in endocytosis from the host and the trafficking of hemoglobin in the parasite (54). The authors also reported that PfPI3-kinase was in part exported to the red blood cell cytosol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Ablation of Vps34 prevents the formation of autophagosomes. 53 The Plasmodium genome encoded one predicted Vps34-type enzyme containing the characteristic domains of class III PtdIns 3-kinases (e.g., a calcium/lipid-binding C2 domain, a PtdIns 3-kinase family accessory domain and a C-terminal PtdIns 3-and PtdIns 4-kinase catalytic domain). Surprisingly, PtdIns3K (the P. falciparum PIK3C3 ortholog) has been shown to localize at the food vacuole and host plasma membrane during the blood stage.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, PtdIns3K (the P. falciparum PIK3C3 ortholog) has been shown to localize at the food vacuole and host plasma membrane during the blood stage. 53 It will be interesting to examine whether Plasmodium PtdIns3K participates in the formation of autophagosomes budding off from the membrane of the apicoplast as described for mitochondria.…”
Section: Discussionmentioning
confidence: 99%